How Medieval Europe was Ruled. Edited by Christian Raffensperger. Abingdon and New York: Routledge, 2024. ISBN 978-1-032-10016-6. Xvi + 242pp. £35.99. - SImon Egan (Royal Studies Journal)
How Medieval Europe was Ruled.  Edited by Christian Raffensperger. Abingdon and New York: Routledge, 2024. ISBN 978-1-032-10016-6. Xvi + 242pp. £35.99.